2020
DOI: 10.1186/s40575-020-00093-9
|View full text |Cite
|
Sign up to set email alerts
|

Dog leucocyte antigen (DLA) class II haplotypes and risk of canine diabetes mellitus in specific dog breeds

Abstract: Background Canine diabetes mellitus (DM) is a common endocrine disease in domestic dogs. A number of pathological mechanisms are thought to contribute to the aetiopathogenesis of relative or absolute insulin deficiency, including immune-mediated destruction of pancreatic beta cells. DM risk varies considerably between different dog breeds, suggesting that genetic factors are involved and contribute susceptibility or protection. Associations of particular dog leucocyte antigen (DLA) class II hap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 59 publications
2
15
0
Order By: Relevance
“…In dogs, strong breed predispositions suggest a genetic component contributes to disease risk 31 . Denyer et al evaluated dog leukocyte antigen (DLA) (the canine equivalent to human leukocyte antigen) haplotypes in diabetic and control dogs (at least 20 in each group for each breed) in 12 different dog breeds 32 . They identified five dog breeds with DLA haplotypes associated with risk or protection, but other dog breeds, including 3 of the breeds at highest risk for diabetes, had no DLA associations with DM.…”
Section: Discussionmentioning
confidence: 99%
“…In dogs, strong breed predispositions suggest a genetic component contributes to disease risk 31 . Denyer et al evaluated dog leukocyte antigen (DLA) (the canine equivalent to human leukocyte antigen) haplotypes in diabetic and control dogs (at least 20 in each group for each breed) in 12 different dog breeds 32 . They identified five dog breeds with DLA haplotypes associated with risk or protection, but other dog breeds, including 3 of the breeds at highest risk for diabetes, had no DLA associations with DM.…”
Section: Discussionmentioning
confidence: 99%
“…In the one-year prevalence study conducted by O’Neill et al [ 26 ] the most common breeds among the incident elbow joint disease were Labrador Retriever ( n = 189, 30.68%), GSD ( n = 43, 6.98%), Staffordshire Bull Terrier ( n = 32, 5.19%) and Rottweiler ( n = 23, 3.73%), along with crossbred dogs ( n = 100, 16.23%).…”
Section: Discussionmentioning
confidence: 99%
“…From dogs older than 6 years included in the mentioned study, 13 out of 16 were Labrador Retrievers, 3 out of 4 were GSDs, 5 out of 6 were Golden Retrievers and 6 out of 8 were mixed-breed dogs. According to O’Neill et al [ 26 ] the median age (in years) at first diagnosis for breeds with over 20 incident was: Labrador Retriever 6.42 (2.50–9.08, n = 188), German Shepherd Dog 5.64 (0.80–7.77, n = 42), Staffordshire Bull Terrier 8.02 (3.16–10.87, n = 32), Rottweiler 7.20 (1.47–8.17, n = 23), English Springer Spaniel 7.00 (1.77–12.27, n = 21), Golden Retriever 9.75 (5.27–11.65, n = 21) and crossbred dogs 7.65 (3.39–10.95, n = 100). However, all dogs with a diagnosis of elbow joint disease made by veterinarians were included in above mentioned study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For several decades the predisposition of some breeds to canine DM has been investigated and reported. Especially Samoyed and Australian terrier have frequently been reported at high risk of development [ 18 , 19 , 21 , 22 , 27 29 ] and the German Shepherd and Boxer at low risk [ 11 , 18 , 22 , 26 – 30 ]. Other studies have indicated that other breeds are at high risk in some countries, e.g.…”
Section: Introductionmentioning
confidence: 99%